Exclusion in the all-pay auction: an experimental investigation - Fehr, Dietmar; Schmid, Julia (Discussion paper, 2017)
Contest designers or managers who want to maximize the overall revenue of a contest (relative performance scheme) are frequently concerned with a trade-off between contest homogeneity and inclusion of contestants with high valuations. In our experimental study, we find that it is not profitable to exclude the most able bidder in favor of greater homogeneity among the remaining bidders, even if the theoretical exclusion principle predicts otherwise. This is because the strongest bidders are willing to give up a substantial part of their expected rent and prefer a strategy that ensures a lower but secure pay-off.
Keywords: Arbeitspapier; Graue Literatur